FACE RECOGNITION TECHNIQUES - Romanyuk, Olexandr N.; Vyatkin, Sergey I.; Pavlov, Sergii V.; Mykhaylov, Pavlo I.; Chekhmestruk, Roman Y.; Perun, Ivan V. (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
The problem of face recognition is discussed. The main methods of recognition are considered. The calibrated stereo pair for the face and calculating the depth map by the correlation algorithm are used. As a result, a 3D mask of the face is obtained. Using three anthropomorphic points, then constructed a coordinate system that ensures a possibility of superposition of the tested mask.